Behavior in the Prevention of COVID-19 in the Elderly after Tele-Nursing - Citra Windani Mambang Sari; Desy Indra Yani; Neti Juniarti (STIKes Hang Tuah Pekanbaru, 2024)
Prevention and management of COVID-19 in the elderly in Indonesia are essential. This is strongly influenced by the knowledge, attitudes and behaviour of the elderly about COVID-19. The elderly are the population most at risk due to COVID-19 transmission. This population requires health education on the prevention and impact of COVID-19 transmission. One of the interventions that can be done is through tele -nursing. This study aimed to identify the knowledge, attitudes and behavior of the elderly to prevent and manage COVID-19 after tele-nursing. This research uses quantitative descriptive on 101 elderly respondents in 26 sub-districts in West Java. The instrument consists of symptoms, knowledge, attitudes and behavior of COVID-19 in respondents who were measured after tele-nursing intervention in the elderly. The analysis uses percentage and frequency distribution. The results of the representative knowledge of respondents are good; only 31.7% of respondents do not know about the 2019 COVID-19 transmission through wild animals and 24.8% when there is no fever. The representation of the respondent's behavior after tele-nursing was nine respondents did not use masks, and 33 still went to crowded places, 33 did not wash their hands after handling objects, and 34 did not avoid touching the face area. The knowledge, attitudes and behavior of respondents illustrate the government's stay-at-home campaign and tele-nursing related to the prevention of COVID 19 in the elderly. Some respondents still have not carried out maximum prevention due to situations and conditions such as the economy, signals, ownership of smartphones. Tele-nursing is one way to improve COVID-19 prevention behavior in the elderly. Further research can be carried out on the elderly by using Randomized Control Trial and qualitative studies to explore factors that influence the involvement of the elderly in the program.